The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.34067/kid.0000302021
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Hemocompatibility of a Novel Polysulfone Dialyzer: A Randomized Controlled Trial

Abstract: Background: High-flux dialyzers shall effectively remove uremic toxins and be hemocompatible to minimize intradialytic humoral and cellular stimulation and long-term impact on patient outcomes. A new dialyzer with a modified membrane surface has been tested for performance and hemocompatibility. Methods: This multicenter, prospective, randomized, cross-over study applied for one week each the new polysulfone-based FX CorAL 600 (Fresenius Medical Care, Bad Homburg, Germany), the polyarylethersulfone-based Polyf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 47 publications
(50 reference statements)
2
29
0
Order By: Relevance
“…The β2-m RRs in the comPERFORM study were somewhat higher (range 72.7–75.5%) than in an earlier study comparing FX CorAL 600 with Polyflux 170H and SUREFLUX-17UX (70.3% and 67.7% for the two dialyzers with synthetic membranes; 51.3% for the cellulose-based dialyzer) [ 13 ]. This difference is explained by different treatment modalities and confirms observations of other authors that higher RRs can be obtained with higher substitution and blood flow rates [ 16 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…The β2-m RRs in the comPERFORM study were somewhat higher (range 72.7–75.5%) than in an earlier study comparing FX CorAL 600 with Polyflux 170H and SUREFLUX-17UX (70.3% and 67.7% for the two dialyzers with synthetic membranes; 51.3% for the cellulose-based dialyzer) [ 13 ]. This difference is explained by different treatment modalities and confirms observations of other authors that higher RRs can be obtained with higher substitution and blood flow rates [ 16 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 64%
“…This difference is explained by different treatment modalities and confirms observations of other authors that higher RRs can be obtained with higher substitution and blood flow rates [ 16 , 21 , 22 ]. In the study reported by Ehlerding et al [ 13 ], substitution flow rates were set manually to around 70 mL/min, whereas in comPERFORM they were automatically set by the dialysis machines and reached a mean of 92 mL/min. In addition, blood flow was slightly higher in the comPERFORM study (∼325 mL/min versus 305 mL/min).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations